Microbiological Contamination Profiling of Geothermal Hot Spring Water at Gambiran Padusan Bath, Pacet District, Mojokerto Regency - Umarudin Umarudin; Ramadhan Renaisansa; Aisyah Hadi Ramadani (Universitas Muhammadiyah Lamongan, 2026)
This study provides an initial microbiological load assessment of Gambiran Padusan Bath hot spring water (36–39°C) using Total Plate Count (TPC) analysis based on ISO 4833-1:2013 standards. Pour plate technique on nutrient agar with 0.9% NaCl, across dilutions 10⁻¹ to 10⁻⁶, yielded 4.84 × 10⁴ CFU/mL from valid plates (25-250 colonies; averages: 219, 168.3, 126.3 CFU). Triplicate plating ensured reproducibility (RSD <10%, CV <15%), with declining counts in higher dilutions (17.7 to 0 CFU) confirming methodological reliability. Endogenous geothermal heat provides intrinsic disinfection, selectively favoring beneficial aerobes over pathogens, aligning TPC below WHO (<10⁵ CFU/mL) and BPAK 2017 recreational limits. Padusan's controlled microbiota poses minimal dermal/opportunistic infection risk during 15-20 min hydrotherapy sessions, supporting musculoskeletal relaxation (20-30% tension reduction), anti-inflammatory mineral absorption, and stress relief via endorphin induction. Logarithmic dilutions and 37±1°C incubation (mimicking skin temperature) optimized mesophile profiling, distinguishing therapeutic safety from bioprospecting. Negative 10⁻⁶ growth rules out hyper-contamination/aerosol risks. This baseline enables temporal monitoring, geotourism capacity planning (max 50 bathers/hour), and sustainable development, bridging public health with enzymatic bioprospecting potentials. Keywords - Hot Spring; Hydrotherapy Safety; Microbial Load; Plate Count; Water Quality